El impacto del cobro excesivo en la notaría del Cantón Baños y su relación con el cumplimiento de los estándares deontológicos y derechos humanos. - Silva Rivera, Alejandra Valeria (2024)
With the present research work which has been titled "The impact of excessive charging in the notary office of Cantón Baños and its relationship with compliance with deontological and human rights standards" focuses on analyzing the consequences generated by excessive charging of notarial fees, if the duties, ethical and moral values that a notary must adhere to are practiced, respecting the fundamental rights related to these legal services which must be performed in an equitable and fair manner. It is important to mention that the single Notary Office of Baños plays a fundamental role in the legal system, but since there is only one notary office in the city, it would be one of the reasons for the excessive charging of notarial fees, this constitutes an abuse on the part of the workers. from the Canton Baños Notary's Office, since the lack of option for users means that they have no alternative but to use the services in this place. This is how this activity harms vulnerable sectors; as are older adults, as well as people with disabilities and low-income people. This research has a qualitative and quantitative approach since we are going to analyze the behaviors of the users and the notary, in order to find the reason for the problem; in which we will handle research techniques, such as the survey that will be a support technique for obtaining real results from people who have been affected by excessive charges, with these we will seek to verify if the reason for the monopoly of the Notary in Baños is the cause. to generate the collection of higher rates than those established. Thus we can investigate the perspectives of the different users, if they consider that promoting transparency in the notarial area or competition would rule out this problem. Keywords: Notaries, improper, excessive, rates, users, collection.